GAMBARAN KUALITAS HIDUP PASIEN KANKER PAYUDARA: LITERATURE REVIEW - Ririn Anggreni; Ririn Muthia Zukhra; Veny Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Breast cancer is the number one deadly disease in women and can affect their quality of life. Quality of life is an individual's perception of his life based on the norms and values in which they live. The purpose of this study was to describe the quality of life of breast cancer patients. This research is a literature review. Sources of search data for published articles using Google Scholar and Pubmed. The search for research articles used the keywords “quality of life and breast cancer patients” and “quality of life and breast cancer”. The inclusion criteria in this study include international articles in English, articles published in 2016-2020. Based on the selection of articles using the screening method, 11 articles were found. The results of this research, 8 out of 11 articles described breast cancer patients had a poor quality of life. The decrease was caused by various factors such as age, body mass index, marital status, menopausal status, education, employment, medication, stage of cancer and self-confidence.Keywords: Cancer; breast cancer; quality of life